Effect of Obstructive Sleep Apnea on Immunity in Cases of Chronic Rhinosinusitis With Nasal Polyps - Dong-Kyu Kim (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2021)
Objectives. Chronic rhinosinusitis with nasal polyps (CRSwNP) is a more severe inflammatory form of CRS that often coexists with obstructive sleep apnea (OSA). However, little is known about the relationship between OSA and the immune profile in patients with CRSwNP. We aimed to investigate the immune profile of patients with CRSwNP according to OSA severity. Methods. This study included 63 patients with CRSwNP and nine control subjects. Protein levels of inflammatory mediators were determined using multiplex immunoassays. All patients underwent standard polysomnography. Results. In patients with eosinophilic CRSwNP (ECRSwNP), interleukin (IL)-6 and chemokine [C-X-C motif] ligand (CXCL)-1 (type 1 immune-related markers) were upregulated in cases of moderate-to-severe OSA. Additionally, IL-4, IL-13, C-C motif chemokine (CCL)-11, CCL-24 (type 2 immune-related markers), and IL-17A (a type 3 immune-related marker) were present at elevated levels in patients with moderate-to-severe OSA. Although there were no significant differences in type 1, 2, or 3 immune-related markers among patients with non-eosinophilic CRSwNP (NECRSwNP) according to the severity of OSA, transforming growth factor-beta expression was higher in those with moderate-to-severe OSA. Furthermore, in ECRSwNP with moderate-to-severe OSA, associations were detected between serum markers and some upregulated inflammatory markers. Conclusion. OSA may increase the heterogeneity of the immune profile (types 1, 2, and 3) in patients with ECRSwNP, but not in those with NECRSwNP.